Formation of Human Resources in the Process of Circumpolar Region Development - Silin, Anatoliy N.; Tkacheva, Nina A. (International Journal of Economics and Financial Issues, 2015)
Article reveals the specific features and problems of human resources formation in oil and gas regions of the Russian Arctic and Subarctic. The research objective is to clarify the correlation of the ‘labor resources’ and ‘human resources’ concepts, identify of mechanisms of their formation, and determine the characteristics and capabilities of the most effective use of human potential through the use of non-traditional methods of organizing production shift in the circumpolar region. Human resources are treated as the most capacious concept with extended space-time and socio-cultural characteristics, additionally containing the hidden features and quality. The factors that determine the specificity of the formation of human resources in the circumpolar region, the inconsistency of regional identity and the perception of further development of the territories of indigenous and newly arrived population are allocated. The study is based on sociological surveys held from 1980 to 2015 covering various population categories of the circumpolar zones: the old-timers, newcomers, shift workers, representatives of indigenous peoples of the north. Research results enable the representatives of public authorities and oil and gas companies understand the effects of exploration and production operations on the way of life of indigenous peoples as well as to develop solutions for combining cultural traditions and modern industrial innovation as to help minimize social and ethno-cultural harm. Additionally, study reveals the features of the shift workers’ interactions with the indigenous population, as well as in labor collectives, define areas of possible constructive dialogue. Expert interviews revealed behavioral features of stationary and shift staff of oil and gas companies, the dynamics shift workers’ assessment of their living standards. The authors consider it necessary to continue research of the social problems arising in the course of development of Arctic regions, to develop a system of standards governing the quality of human resources, and quality of life. Keywords: shift method, autochthonous population, regional identity, arctic region JEL Classifications: Q3; M54; J6; R11